A Clinical Score, Including Biohumoral Parameters, Is a Useful Pretest Index to Discriminate Pulmonary Infections from Radiation Damage in Chemoradiation-Treated Lung Cancer Patients. (21st May 2014) - Ramella, Sara; Spoto, Silvia; Fiore, Michele; Grasso, Giovanna; Campanale, Roberto Erasmo; Ippolito, Edy; Greco, Carlo; Iurato, Aurelia; Trodella, Luca Eolo; Cortigiani, Marco; Trodella, Lucio; D'Angelillo, Rolando Maria; et al.
Abstract : To obtain an easy and prompt differential diagnosis between lower airways infections and acute radiation pneumonitis in chemoradiation lung cancer patients. From 303 patients treated, only patients with severe pulmonary symptoms were hospitalized. Clinical and radiation scores were calculated evaluating clinical, biohumoral, dosimetric parameters. Out of 36 patients hospitalized, infections and acute radiation pneumonitis were reported in 66.7% and 33.3%, respectively. Patients with clinical score ≥2 had an Odds Ratio of 3.4 (1.4–8.3; p = .006) to have infectious pneumonia, while radiation score was not predictive.